2022
DOI: 10.3389/fphar.2022.977726
|View full text |Cite
|
Sign up to set email alerts
|

Tetraclinis articulata (vahl) masters: An insight into its ethnobotany, phytochemistry, toxicity, biocide and therapeutic merits

Abstract: Tetraclinis articulata (Vahl) Masters, commonly known as Sandarac tree and Araâr, is the only species representing the genus Tetraclinis Masters. The plant has been extensively used for medicinal, artistic, and ritual purposes since its first recorded use in 1800 B.C. Recently, a full range of ethnobotanical investigations has been undertaken to document the plant’s empirical knowledge. They reported the use of different parts, such as leaves, stems, cones, bark, and roots, as part of folk healing practices to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 102 publications
1
8
0
Order By: Relevance
“…Masters used in the treatment of nervous, respiratory, dermatology, digestive ailments. Indeed, these results are consistent with Khatib et al 50 work which found that stomach pain, respiratory and intestinal infections, diabetes and hypertension were the most frequently treated diseases by Tetraclinis tree. in this sense, the work of Rached et al 51 evaluated the in vitro anti-inflammatory potential of the aqueous extract of T. articulata leaves on lipopolysaccharides (LPS)induced nitric oxide (NO) production by murine macrophages.…”
Section: Usage Values Of Species and Familiessupporting
confidence: 92%
See 2 more Smart Citations
“…Masters used in the treatment of nervous, respiratory, dermatology, digestive ailments. Indeed, these results are consistent with Khatib et al 50 work which found that stomach pain, respiratory and intestinal infections, diabetes and hypertension were the most frequently treated diseases by Tetraclinis tree. in this sense, the work of Rached et al 51 evaluated the in vitro anti-inflammatory potential of the aqueous extract of T. articulata leaves on lipopolysaccharides (LPS)induced nitric oxide (NO) production by murine macrophages.…”
Section: Usage Values Of Species and Familiessupporting
confidence: 92%
“…People aged 40-49 years have the highest frequency of use of medicinal plants with a percentage of 44,33%. The age groups [50][51][52][53][54][55][56][57][58][59], [<30], and [30][31][32][33][34][35][36][37][38][39] come next with a percentage of 21,65%, 14,43%, and 12,37%, respectively, while the age group not well represented is the respondents over 60 years old (7,22%) (Table 1). These results show that the distribution of ethnomedical know-how is clearly visible across the different age groups, including those under 30 years of age, which attests to the persistence of natural and traditional treatments and the durability of knowledge transmission from one generation to the next 31 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, most of these studies have tended to use disc diffusion assay, which is unreliable for measuring antimicrobial activity since the compounds’ polarity impact how effectively they diffuse into the polar agar medium and consequently alter the inhibition zone size. In contrast, agar dilution and broth microdilution methods enable precise quantitative conclusions by determining MIC values for antimicrobials ( Khatib et al, 2022b ). Therefore, they are highly recommended in future studies for regular antimicrobial susceptibility testing.…”
Section: Discussionmentioning
confidence: 99%
“…Ethnoveterinary medicine (EVM) refers to a complex multifaceted system of beliefs, skills, techniques, and practices used to prevent, treat, and promote the health of husbandry livestock and other income-generating animals ( McGaw and Eloff, 2008 ; McGaw and Abdalla, 2020 ). Even though these practices have steadily been handed down across generations, a myriad of ethnoveterinary surveys stated that the know-how pertaining to livestock healthcare is mainly retained by elderly people ( Bartha et al, 2015 ; Jamil Ahmed and Murtaza, 2015 ; Eiki et al, 2021 ; Güler et al, 2021 ; Khatib et al, 2022b ). Thereby, this ancestral medical wealth may be doomed to disappear with the death of their practitioners.…”
Section: Ethnoveterinary Applicationsmentioning
confidence: 99%